Microbubbles bound to drug-eluting beads enable ultrasound imaging and enhanced delivery of therapeutics - Owen, J; Negussie, AH; Burks, SR; Delgado, J; Mikhail, AS; Rivera, J; Pritchard, WF; Karanian, JW; Stride, E; Frank, JA; Wood, BJ (Nature Research, 2024)
Transarterial chemoembolization (TACE) is an image-guided minimally invasive treatment for liver cancer which involves delivery of chemotherapy and embolic material into tumor-supplying arteries to block blood flow to a liver tumor and to deliver chemotherapy directly to the tumor. However, the released drug diffuses only less than a millimeter away from the beads. To enhance the efficacy of TACE, the development of microbubbles electrostatically bound to the surface of drug-eluting beads loaded with different amounts of doxorubicin (0–37.5 mg of Dox/mL of beads) is reported. Up to 400 microbubbles were bound to Dox-loaded beads (70–150 microns). This facilitated ultrasound imaging of the beads and increased the release rate of Dox upon exposure to high intensity focused ultrasound (HIFU). Furthermore, ultrasound exposure (1 MPa peak negative pressure) increased the distance at which Dox could be detected from beads embedded in a tissue-mimicking phantom, compared with a no ultrasound control.